Evaluasi Situs Web Covid19.Kaltimprov.go.id sebagai Penyebaran Informasi Pandemi Covid-19 di Provinsi Kalimantan Timur - Bambang Irawan; Muhammad Hidayat (Research and Development Agency Ministry of Home Affairs, 2021)
Global pandemic has affected all sectors of human life.. Aside from struggling to contain the spread of the disease, one of the biggest challenges of any government around the world is to prevent the dissemination of fake information regarding covid-19. Fake information not only dangerous for the people because they can cause psychological issues, but the most important thing is they can nullify government’s strategic policy of covid containment. For that reason, dissemination of accurate and official information for all citizens is vital. In order to do so, the government has to maximize the instrument of communication channel, and one primary example is government website. The official website has to meet several criteria for carrying the tasks, and for that it is important to evaluate them. In this occasion we will evaluate the official website of covid19.kaltimprov.go.id as the primary source of any information related to the pandemic in Kalimantan Timur. We are using SortSite 5.3.5 software, an online-based website evaluating tools. The software will evaluate four variables, they are: errors, accessibility, compatibility and standards. Based on the result, we find that in covid19.kaltimprov.go.id, the problem is centered on the accessibility with 85% of issues followed by compatibility and standards with 72% while the last variable, errors, scored 71%. This result gives the signal that there is something wrong with the website because the number of problems or issues on each variable is more than 50%, and it could impact the success of government program in tackling fake information.